2006
DOI: 10.1055/s-2006-948230
|View full text |Cite
|
Sign up to set email alerts
|

Communication in Young Children with Motor Impairments: Teaching Caregivers To Teach

Abstract: Communication between caregivers and children with moderate to severe motor impairments is a tremendous challenge, and one that deserves attention as a central component of early intervention programs. This article examines a caregiver-training program that explored key elements to creating strong communicative interactions between young children with moderate to severe motor impairments and their primary caregiver. Three caregiver-child dyads participated in a 3-week treatment program teaching caregivers how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Some behaviors and skills are notably harder to teach caregivers and may require the expertise of a trained professional. Olswang et al (2006), for example, demonstrated that scaffolding children’s performance to TG is difficult for caregivers to learn, even when given direct instruction. Because no single approach can serve all needs, birth-to-three providers must select the most appropriate treatment and service delivery model to match a child’s current and emerging developmental profile, as well as family needs and preferences (Brady, Warren, & Sterling, 2009; Prelock, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some behaviors and skills are notably harder to teach caregivers and may require the expertise of a trained professional. Olswang et al (2006), for example, demonstrated that scaffolding children’s performance to TG is difficult for caregivers to learn, even when given direct instruction. Because no single approach can serve all needs, birth-to-three providers must select the most appropriate treatment and service delivery model to match a child’s current and emerging developmental profile, as well as family needs and preferences (Brady, Warren, & Sterling, 2009; Prelock, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested the value of teaching this same protocol to caregivers of three children with physical disabilities (Olswang, Pinder, Hanson, 2006). After six sessions, caregivers demonstrated the ability to provide opportunities for communication and recognize gaze attempts, although they were minimally able to shape TG.…”
Section: Early Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that SLPs need to clearly advise caregivers on appropriate behaviors to emphasize during interactions with their children. Further, results of earlier work by Olswang et al(2006) have shown that scaffolding children’s performances to TG is difficult for parents to learn, even when they are provided with direct instruction. This evidence suggests the importance of being able to clearly identify the behavioral objectives and the means by which to teach them.…”
Section: Discussionmentioning
confidence: 99%
“…For those children who have adequate vision but are constrained by motor and other sensory limitations, gaze is viewed as an important conventional signal of communication to target in treatment (Woods & Wetherby, 2003; Wetherby et al, 1989; Pinder, Olswang, & Coggins, 1993; Pinder & Olswang, 1995; Olswang, Pinder, & Hanson, 2006). This is particularly true for children who may later require augmentative and alternative communication strategies (Goossens’ & Crain, 1987).…”
Section: Impact Of Severe Disabilitiesmentioning
confidence: 99%